2021
DOI: 10.1093/brain/awab174
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal deletion of Wwox, associated with WOREE syndrome, causes epilepsy and myelin defects

Abstract: WOREE syndrome caused by human germline biallelic mutations in WWOX is a neurodevelopmental disorder characterized by intractable epilepsy, severe developmental delay, ataxia and premature death at the age of 2–4 years. The underlying mechanisms of WWOX actions are poorly understood. In the current study, we show that specific neuronal deletion of murine Wwox produces phenotypes typical of the Wwox-null mutation leading to brain hyperexcitability, intractable epilepsy, ataxia and postnatal lethality. A signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 58 publications
5
36
0
Order By: Relevance
“…Since a major part of the phenotype was observed in the cortical areas of the COs, and since a recent paper has demonstrated a major role for WWOX in the cortex (Repudi et al , 2021 ), we decided to employ a cortex‐specific protocol and generate forebrain organoids (FOs) (Qian et al , 2016 , 2018 ). First, to validate reproducibility, we generated FOs from WSM F1 and WSM S5 and found comparable phenotypes for WSM COs (Appendix Figs S4F and G, and S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since a major part of the phenotype was observed in the cortical areas of the COs, and since a recent paper has demonstrated a major role for WWOX in the cortex (Repudi et al , 2021 ), we decided to employ a cortex‐specific protocol and generate forebrain organoids (FOs) (Qian et al , 2016 , 2018 ). First, to validate reproducibility, we generated FOs from WSM F1 and WSM S5 and found comparable phenotypes for WSM COs (Appendix Figs S4F and G, and S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, we found that conditional ablation of murine Wwox in either neural stem cells and progenitors (N-KO) or neuronal cells (S-KO mice) resulted in severe epilepsy, ataxia, and premature death at 3-4 weeks, recapitulating the phenotypes observed in the Wwox-null mice (Repudi et al, 2021). These results highlight the significant role of WWOX in neuronal function and prompted us to test whether restoring WWOX expression in the neuronal compartment of Wwox-null mice could reverse the observed phenotypes.…”
Section: Introductionmentioning
confidence: 79%
“…Chronic inflammation in the brain occurs due to increased activation of GSK-3β for causing epileptic seizure, and upregulation of microglia cells and astrocytes and reduced GABG-ergic inhibitory interneurons in the brain cortex and hippocampus [ 61 ]. Together, WWOX deficiency in newborns suffer the disorder of sex differentiation (DSD), spinocerebellar ataxia (SCA), early infantile epileptic encephalopathy (EIEE), and WWOX -related epileptic encephalopathy (WOREE syndrome) [ 60 , 61 , 62 , 63 , 69 , 70 , 71 , 72 , 73 ]. WWOX controls neuronal differentiation, and that loss of WWOX induces activation of GSK-3β that contributes to neurodegeneration [ 49 ].…”
Section: Wwox In Alzheimer’s Diseasementioning
confidence: 99%
“…Despite WWOX being a defined risk factor for AD [ 38 ], functional WWOX is needed to support the development of neural system and maintain normal neuronal physiology. Presence of dysfunctional WWOX, loss of WWOX, or excessive WWOX causes neurodegenerative diseases and neuronal death such as in AD [ 7 , 28 , 41 ], WOREE [ 60 , 61 , 62 , 63 , 69 , 70 , 71 , 72 , 73 ], sciatic nerve damage [ 42 , 96 ], retinal degeneration [ 68 ], and Parkinson’s disease [ 97 ].…”
Section: Conclusion and Perspectives For The Futurementioning
confidence: 99%
See 1 more Smart Citation